KONSEP SUNNAH DALAM PERSPEKTIF MUHAMMAD SYAHRUR Suatu Pembacaan Baru Dalam Kritik Hadis - Ardiansyah Ardiansyah (State Islamic University North Sumatra, 2009)
Abstract: The Concept of Sunna in the Pespective of Muhammad Syahrur: A New Reading on Hadith Critism. The development of hadits critisism dircourses has been an interesting issue in Islamic studies. Since the early period of Islam, scholars was constructed and developed methodology that would become the standard for qualification of hadith applicable in the succeeding generation. However, in this contemporary period, studies on Hadith is very contrast to the early period like what Muhammad Syahrur, a prominent Syirians scholar has done. According to Syahrur, the Prophet’s saying and deeds are the product of history rather than revelation. He claimed that whatever hadiths that are contradictory to al-Qur’an must be rejected, although related to religious observance or moral conduct. In this article, the author attemps to explore the controversial thought of Muhammad Syahrur.Kata Kunci: kritik, hadis